Cocreating Collaborative Leadership Learning Environments: Using Adult Learning Principles and a Coach Approach. Issue 156 (7th December 2017) - Page, M. Beth; Margolis, Rhonda L.
Abstract: As educators, we seek to answer the following question: "What magic can happen when you believe that people are whole and resourceful and you hold the space for generative, collective wisdom?" This chapter explores collaborative leadership and learning with adult learners. We focus on creative ways to optimize learning and enhance capacity to lead self and others.